TTGO LORA ESP32: SOLUSI NIRKABEL UNTUK PROTOTIPE PENGENDALIAN PENGINJEKSI ARUS PADA METODE GEOLISTRIK - Nurpadillah, Sifa; Susanto, Kusnahadi; Mukhtar, Husneni; Cahyadi, Willy Anugrah; Ikhsan, Akhmad Fauzi; Nurdin, Agung Ihwan; Razzak, Taufiq Abdul; Rahmawati, Dien (TEKTRIKA, 2023)
Rock resistivity properties obtained using the geo-electric method are used to estimate subsurface soil structures and rock types in geophysical exploration. The data collection process using this geoelectrical method is often carried out in remote areas by installing current electrodes (AB) and potential electrodes (MN) up to 1.5 km away. The success of exploration is highly dependent on the current injection source used. The greater the current used, the deeper exploration that can be carried out. However, the required distance between AB and MN electrodes is getting further and the ABMN electrodes are connected by a cable. This causes the process of collecting data at further distances of electrodes to become more complex. This study discusses a current source prototype for geo-electric methods that can communicate wirelessly with TTGO LoRa ESP32 as a controller. This prototype provides three injection power options: full, medium, and low. Current injection is carried out on a dummy resistor, which acts as earth. When injecting current into the dummy resistor, current measurements obtained using the INA219 sensor gave very consistent measurement results because it had a relative error of < 1% (on 50 ? and 300 ? dummy resistors). When measuring a current of 0.0066 A, the relative error increases to 1.5%. But it still shows good consistency in the INA219 measurement results. In addition, the MAPE for all measurements is within < 10%, which means that the INA219 readings provide excellent results. Key Words: current injector, geo-electrical, INA219, voltage divider, TTGO LoRa.